Aureliza Alves do Nascimento (1927-1971) em busca do recomeço: mulher, prostituição e violência em terras jorge-amadianas - Barbosa, Luciana Santos (2010)
This research revolves around matters of gender, oral tradition and literature. The life story of Aureliza Alves do Nascimento is entwined with the fictitiouns tales written by Jorge Amado, a baiano book writer. Aureliza did not accept the reality imposed upon her nor the humiliation of having been betrayed by her husband in the small town of Ibicaraí, south of Bahia. She decided to restart her life in the Great São Paulo, and temporarily left her children behind. Her journey towards freedom and a new life only ended when she reunited with them, not without facing all sorts of setbacks generated by sexist relationships still faced by women both in São Paulo and Bahia